Aruṭtiru Taṉināyakam Aṭi̲kaḷār niṇaivu malar, 1981 Jaṉavari 10 - Kanagarasan, M., 1942-; Puṉitaliṅkam, Es (Makkaḷ Kural Veḷiyīṭu, 1981)
Souvenir published to commenorate Xavier S. Thani Nayagam, Tamil litterateur who founded the International Association of Tamil Research; comprises articles on his life and contribution to Tamil language and literature.